Biotinylated N-palmitoyl chitosan for design of drug loaded self-assembled nanocarriers. (August 2016) - Balan, Vera; Redinciuc, Valentina; Tudorachi, Nita; Verestiuc, Liliana
Graphical abstract: Highlights: N-palmitoyl chitosan is biofunctionalized with biotin, via carbodiimide chemistry. Biotinylated N-palmitoyl chitosan is able to self-assemble as nanocarriers. Chemotherapeutic agents are entrapped simultaneously with nanocarrier generation. Nanoparticles exhibit a pH-dependent release profile, biodegradability and hemocompatibility. Abstract: Owing to its remarkable properties, biotin has been proposed as a very active targeting molecule in anti-cancer formulations. In this study, biotinylated N-palmitoyl chitosan has been prepared and investigated as suitable polymeric derivative for preparation of docetaxel self-assembled nanocarriers with applications in breast cancer treatment. Biotinylated N-palmitoyl chitosan has been obtained through the reaction of N-palmitoyl chitosan with biotin, via carbodiimide chemistry; its structure has been confirmed by FT-IR, 1 H NMR spectroscopy and thermal analyses. The self-aggregation behaviour of the polymer in aqueous was determined using fluorescence spectroscopy. Docetaxel loaded self-assembled nanoparticles based on biotinylated N-palmitoyl chitosan, prepared by combining the dialysis method with ultrasonication, were nearly spherical in shape, with narrow size distribution, in the range of 300–400 nm and positive charged. Nanoparticles exhibited a good drug loading ability and a pH-dependent release profile of drug, susceptibility to biodegradation and hemocompatibility, properties which can be exploited in drug delivery applications.